Exposure to Mental Health Training and Variations in Work Strain, Coping, and Positive Mental Health in the Canadian Military. (2nd April 2020) - Lee, Jennifer E. C.; Boulos, David; Sudom, Kerry
Abstract: Promoting adaptive coping has been a central objective of mental health training for enhancing resilience. A multi-group path analysis was conducted on 2013 Canadian Forces Mental Health Survey data to assess the indirect effect of work strain on positive mental health (PMH) through coping among Canadian Armed Forces Regular Force members who either received or did not receive mental health training in the past 5 years ( N  = 6696). Results pointed to a more frequent use of positive coping and a higher level of PMH among those with mental health training exposure. Work strain was associated with using less adaptive coping strategies (i.e., less frequent use of positive coping, more frequent use of negative coping) and, along with such coping strategies, predicted lower PMH. Furthermore, results revealed an indirect effect of work strain on PMH through coping. However, the magnitude of these associations varied little by mental health training exposure. Results support the view that work strain can diminish personal resources and thereby negatively impact coping, and thus underscore the importance of providing service members with access to support programs and services to help them through stressful situations.